Anal excision of perianal fibroadenoma: Expect the unexpected - Eberspacher, Chiara (SAGE Open Med Case Rep, 2021)
Breast fibroadenomas are a common benign tumour in women that may need to be surgically excised. A mammary-like fibroadenoma can exceptionally be found in the pathological report after an anal polyp removal. A 60-year-old woman presented with huge anal polyp of 25 mm. It was surgically removed transanally. Histologic examination revealed a breast fibroadenoma pattern with glandular structures. Proctologist specialists must be aware that mammary-like tumours are a possible differential diagnosis for anal masses despite their rarity in the literature.